The Influence of Oblique Angle Forced Exercise in Surgically Destabilized Stifle Joints Is Synergistic with Bone, but Antagonistic with Cartilage in an Ovine Model of Osteoarthritis. (27th February 2017) - Hill, Rachel J.; Mason, Holly M.; Yeip, Gavin; Merchant, Samer S.; Olsen, Aaron L.; Stott, Rusty D.; Van Wettere, Arnaud J.; Bressel, Eadric; Mason, Jeffrey B.
Abstract : Large animal models of osteoarthritis are a necessary testing ground for FDA approval of human medicine applications. Sheep models have advantages over other available large animals, but development and progression of osteoarthritis in sheep is exceedingly slow, which handicaps progress in development of potential treatments. We combined oblique angle forced exercise to increase stress on the stifle, with surgical destabilization to hasten the development of osteoarthritis in ewes. Methods for early detection of clinical signs included radiography, urine, and serum biomarker assays and gait analysis and ex vivo we used microcomputed tomography and macroscopic joint analysis. Our model was able to produce clinically detectable signs of osteoarthritis in a relatively short period (14 weeks). Changes in bone were highly correlated between microcomputed tomography and radiographic analysis and changes in cartilage correlated well between urinary glycosaminoglycan levels and serum aggrecanase analyses. Exercise improved the negative effects of destabilization in bone but exacerbated the negative effects of destabilization in cartilage. These observations suggest that we may need to consider treatments for bone and cartilage separately. These results represent an improved large animal model of osteoarthritis with rapid onset of disease and superior detection of bone and soft tissue changes.